On the need for integrating cancer into the One Health perspective. (8th October 2021) - M. Dujon, Antoine; Brown, Joel S.; Destoumieux‐Garzón, Delphine; Vittecoq, Marion; Hamede, Rodrigo; Tasiemski, Aurélie; Boutry, Justine; Tissot, Sophie; Alix‐Panabieres, Catherine; Pujol, Pascal; Renaud, François; Simard, Frédéric; et al.
Summary: Recent pandemics have highlighted the urgency to connect disciplines studying animal, human, and environment health, that is, the "One Health" concept. The One Health approach takes a holistic view of health, but it has largely focused on zoonotic diseases while not addressing oncogenic processes. We argue that cancers should be an additional key focus in the One Health approach based on three factors that add to the well‐documented impact of humans on the natural environment and its implications on cancer emergence. First, human activities are oncogenic to other animals, exacerbating the dynamics of oncogenesis, causing immunosuppressive disorders in wildlife with effects on host–pathogen interactions, and eventually facilitating pathogen spillovers. Second, the emergence of transmissible cancers in animal species (including humans) has the potential to accelerate biodiversity loss across ecosystems and to become pandemic. It is crucial to understand why, how, and when transmissible cancers emerge and spread. Third, translating knowledge of tumor suppressor mechanisms found across the Animal Kingdom to human health offers novel insights into cancer prevention and treatment strategies.